Study of phenolic compound of some leaves of species of genus L.Jasminum growing in Iraq - Jawad Kadhim Ali (Al-Qadisiyah Journal of Pure Science, 2018)
The current research has dealt with some species of genus Jasminum L. developing Iraq's chemical study it was identified and diagnosed some phenolic compounds and flavonoids for five species of genus which J.grandiflorum L.,J.officinale L.,J.mesnyi Hance,J.sambac(L.)Aitand J.multiflorum(N.L. Burman )Andrews. The existence of two speciess of important phenolic compounds study has shown a Oleuropein and Coumarins and four speciess of vehicles phlavonoids which Quercetin ,Kaempherol ,Leuteolin and Rutin in all species except speciesJ.grandiflorum It found that contains three compounds only and are the Coumarins of phenols and the Kaempherol and Rutin of flavonoids . It also said the current study, the presence of variations in the concentrations of these substances between species and significantly boosted important taxonomic for this study and take such as manuals taxonomic isolated and separated from each other as distinguish speciesJ.sambac possessing a lower concentration of the compound Oleuropein compared with other compounds found in this species compound. The record speciesJ.officinole highest concentration of three phenolic compounds which Oleuropein ,Quercetin and Rutin, boosting the case slops clearly from the rest of the species under study OPENING STATEMENTS: - Jasminum L., a chemical study, flavonoids, phenolic compounds